Pitch and Revelation Reconfigurations of Reading, Poetry, and Philosophy through the Work of Jay Wright - Daddario, Will (punctum books, 2022)
Pitch and Revelation is the first book-length study of the poetry, prose, and dramatic literature of the African American poet Jay Wright (1934-). The authors premise their reading on joy as foundational philosophical concept. In this, they follow Spinoza, who understood joy as that affect necessary for the construction of intellectual love of God, leading into the infinite univocity of everything. Similarly, with Wright, joy leads to a visceral sense of what the authors call the great weave of the world. This weave is akin to the notion of entanglement made popular by physicists and contemporary scholars of Science Studies, such as Karen Barad, which speaks of the always ongoing, mutually constitutive connections of all matter and intellectual processes. By exhibiting and detailing the joy of reading Wright, Pitch and Revelation intends to help others chart their own paths into the intellectual, musical, and rhythmical territories of Wright's world so as to more fully experience joy in the world generally. Although the exhibitions of meaning making presented are instructive, but they do not follow the "do as I do" or "do as I say" model of instructional texts. Instead,they invite the reader to "do along with us" as the authors make meaning from selections across Wright's erudite, dense, rhythmically fascinating, endlessly lyrical, highly structured, and seemingly hermetic body of work.